2019
DOI: 10.24914/jeb.v22i1.2036
|View full text |Cite
|
Sign up to set email alerts
|

Desentralisasi fiskal dan probabilitas terjadinya korupsi: Sebuah bukti empiris dari Indonesia

Abstract: Tujuan riset ini adalah untuk menguji pengaruh desentralisasi fiskal terhadap probabilitas terjadinya korupsi di pemerintah daerah. Riset ini menggunakan data panel, yaitu data korupsi yang telah berkekuatan hukum tetap (inkracht) dari Mahkamah Agung untuk kasus korupsi yang terjadi pada Anggaran Pendapatan dan Belanja Daerah tahun anggaran 2010-2013. Unit analisis riset ini adalah pemerintah daerah provinsi. Total sampel riset ini sebanyak 132 pemerintah daerah. Variabel desentralisasi fiskal diukur menggunak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 16 publications
(26 reference statements)
1
10
0
6
Order By: Relevance
“…A positive correlation between regional independence and corruption showed that the more independent the region, the higher the probability of corruption in the local government. This study finding is in line with the discovery of the studies conducted by Chang & Geoffrey (2002), Syurmita (2014), Setyaningrum & Safitri (2012), Maria et al (2018), Maria et al (2019a) that independent region tended to commit fraud or corruption in their regional budgets. This is because the uptake of the budget would be more widely used to fund personnel expenditure rather than for regional development activities and/or public service activities.…”
Section: The Effect Of Regional Independence On the Probability Of Corruption In The Local Governmentssupporting
confidence: 90%
See 2 more Smart Citations
“…A positive correlation between regional independence and corruption showed that the more independent the region, the higher the probability of corruption in the local government. This study finding is in line with the discovery of the studies conducted by Chang & Geoffrey (2002), Syurmita (2014), Setyaningrum & Safitri (2012), Maria et al (2018), Maria et al (2019a) that independent region tended to commit fraud or corruption in their regional budgets. This is because the uptake of the budget would be more widely used to fund personnel expenditure rather than for regional development activities and/or public service activities.…”
Section: The Effect Of Regional Independence On the Probability Of Corruption In The Local Governmentssupporting
confidence: 90%
“…Uptake of funds in the autonomous areas is more widely used to fund personnel expenditure than for regional development activities and/or public service activities (CICA, 1997;Setyaningrum & Safitri. F, 2012;Syurmita, 2014;Maria et al, 2019a). Therefore, to examine the relationship between regional independence and corruption in the local governments, Indonesia, the second hypothesis of this study is stated as follows: H2: When the local governments are in an independent condition, the probability of corruption is increasing.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, in some countries, it is found that the level of corruption is getting higher after the implementation of fiscal decentralization (Isufaj, 2014). Crook & Sverrisson (2001), Wu (2005), Chêne (2007), Liu (2007), and Maria et al (2019), in his research, found that fiscal decentralization has a positive impact on increasing corruption in the regions, rather than producing improvements in the quality of public services. Fiscal decentralization without support supported by Good Public Governance mechanism will only produce a corrupt government.…”
Section: Introductionmentioning
confidence: 96%
“…This proves that the implementation of decentralization in Indonesia has an ambiguous impact. On the one hand, the implementation of decentralization makes regions more responsive and flexible in providing public services, but on the other hand, the application of this policy makes corrupt practices occur not only in the central government but also spread to local governments (Akbar, 2013;Anan, 2012;Hartanto & Probohudono, 2013;Hill, 2012;Holtzappel & Ramstedt, 2009;Kuncoro, 2006;Maria et al, 2019;Puspasari & Suwardi, 2016;Rinaldi et al, 2007;Syarif, 2017;Utami, 2018).…”
Section: Introductionmentioning
confidence: 99%